Comparative Antioxidant Capacity of Seed and Fruit Ethanol Extracts of Bitter Melon (Momordica charantia L.) Using FRAP Assay - Ariani, Luysi; Rasyid, Faradiba Abdul; Yuliana, Dewi; Rahmawati, Rahmawati; Muflihunna, Andi; Syarif, Rezki Amriati; Amin, Asni (Journal of Experimental and Clinical Pharmacy (JECP), 2026)
Momordica charantia L. (bitter melon) is traditionally consumed as both food and medicine in Indonesia. Its fruit and seeds contain bioactive compounds such as saponins, flavonoids, polyphenols, and unsaturated fatty acids with recognized antioxidant potential. This study compared the antioxidant activity of ethanol extracts from bitter melon seeds and fruit using the Ferric Reducing Antioxidant Power (FRAP) assay. Extraction was conducted by ultrasound-assisted extraction (UAE) with ethanol as solvent, and antioxidant activity was expressed as quercetin equivalents (mg QE/g extract). The seed extract showed an antioxidant value of 8.680 mg QE/g, while the fruit extract exhibited 8.626 mg QE/g. The statistical analysis showed that the p-value was greater than 0.05, indicating no significant difference between the two extracts. This suggests that both extracts exhibit comparable antioxidant activity. These results highlight that both seeds and fruit of M. charantia may serve as promising natural antioxidant sources for functional food and pharmaceutical applications.